Heat Shock Protein 60 Antibodies Are Associated With a Risk Factor for Cardiovascular Disease in Bedridden Elderly Patients - Jonas Bernardes de Lima Filho; Letícia Freire; Eliana Aguiar Petri Nahas; Fábio Lera Orsatti; Claudio Lera Orsatti (Frontiers in Molecular Biosciences, 2020)
Frailty, in elderly people, represents multiple deficiencies in different organs and is characterized by decreased physiological reserves and greater vulnerability to stressors. Bedridden elderly, with cardiovascular disease (CVD), have a worse prognosis than non-bedridden patients. Heat-shock proteins (HSPs) are molecular chaperones that under physiological conditions facilitate the transport, folding and assembly of proteins. Serum HSP 60-kDa concentrations and their antibodies are increased, in response to non-physiological conditions, suggesting the involvement of HSPs and their antibodies in the development of CVD. The aim of this work was to evaluate heat shock protein 60 and anti-HSP60 antibody levels, associated with a risk factor for cardiovascular disease, in bedridden elderly patients. Clinical, analytical and cross-sectional analyses were performed with 57 elderly (>65 years). HSP60 and anti-HSP60 plasma levels were measured by ELISA. Bivariate analysis using a linear regression model adjusted for risk factors used Framingham Score. Among the 57 elderly, with an average age of 69.89 years, 39% are bedridden; 26% with pre-existing cardiovascular disease and 44% are dyslipidemic. The relationship of risk factors in the Framingham Score was positive for the anti-HSP60 antibody (p = 0.042) measurement. Our data show a positive correlation among the elevation of the Framingham score and the profile of anti-HSP60 antibodies. These results suggest a greater immune activation that is associated with cardiovascular risk and bedridden fragility.